Clinical signs and symptoms associated with acute HIV infection from an intensely monitored cohort on 2 continents. Issue 5 (4th February 2022) - Letizia, Andrew G.; Eller, Leigh Anne; Bryant, Christopher; Dawson, Peter; Nitayaphan, Sorachai; Kosgei, Josphat; Kibuuka, Hannah; Maganga, Lucas; Kroon, Eugène; Sriplienchan, Somchai; Michael, Nelson L.; O'Connell, Robert J.; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Define the clinical presentation of acute human immunodeficiency virus infection (AHI) among men and women from 2 continents to create a clinical scoring algorithm. Comparison of incident sign and symptom between those with and without AHI. At-risk human immunodeficiency virus (HIV) negative men and women in Thailand, Kenya, Tanzania, and Uganda underwent twice-weekly testing for HIV. Newly diagnosed participants were evaluated twice weekly for 21 days after infection. Of the 3345 participants enrolled, 56 African females and 36 biological males from Thailand were diagnosed with AHI. Four hundred fifty-two of their encounters were compared to 18, 281 HIV negative encounters. Due to a high degree of heterogeneity among incident symptoms, 2 unique subgroups based upon geography and sex were created. Among Thai males, the signs and symptoms with the greatest odds ratio (OR) between AHI and uninfected participants were nausea (OR 16.0, 95% confidence interval [CI] 3.9–60.2, P < .001) and lymphatic abnormalities (OR 11.8, 95% CI 4.2–49.0, P < .001); and among African females were pain behind the eyes (OR 44.4, 95% CI 12.0–158.0, P < .0001) and fatigue (OR 22.7, 95% CI 11.3–44.3, P < .001). The Thai male scoring algorithm had a 66% sensitivity and 84% specificity while the African female algorithm had a sensitivity of 27% and specificity of 98%. The different incident symptoms during AHI necessitated creating 2 different scoring algorithms that can guide diagnostic testing among a particular sex in the appropriate geographic setting. Further research on risk exposure, sex, and demographic specific models is warranted.